The Reliabilities of Radiographic Measurements of Cervical Sagittal Alignment in Ankylosing Spondylitis - Shin, Jong Ki; Lee, Jung Sub; Kang, Sung Shik; Lee, Jae Myung; Youn, Bu Hyun (Clinical spine surgery, 2016)
This is a prospective study design. To test the interobserver and intraobserver reliabilities of 5 specific measures of global cervical sagittal alignment in patients with ankylosing spondylitis (AS), and to suggest a better means of measuring cervical sagittal alignment. The intraobserver and interobserver reliabilities of several different methods of measuring cervical lordosis have been reported. However, they have not been studied till yet in patients with AS. Interobserver and intraobserver reliabilities of 5 specific measures of cervical lordosis were evaluated in patients with AS. Eighty patients with AS were allocated to a nonankylosis or an ankylosis group, and the reliabilities of the Cobb C1-C7, Cobb C2-C7, centroid, posterior tangent, and Ishihara index methods were evaluated. The intraclass and interclass correlation coefficients (ICCs) of all 5 methods were generally high. For the 80 study subjects, ICCs were ≥0.84 (excellent) for all 5 radiographic methods. However, comparison of the ICCs, 95% confidence intervals, and mean absolute differences (MAD) between groups with varying degrees of ankylosis showed that the reliability of lordosis measurements decreased as the severity of ankylosis increased. The 5 methods consistently demonstrated higher ICCs for both interobserver and intraobserver comparisons in the nonankylosis group. However, in the ankylosis group, the Cobb C1-C7 method demonstrated high ICCs for both interobserver and intraobserver comparisons, whereas the other 4 methods had high ICCs only for intraobserver comparisons. The intraobserver MADs were similar for the 5 methods (2.4-3.9), but the interobserver MADs of measurement methods in both groups showed low measurement reliability except for the Cobb C1-C7 methods. This study provides a reliability analysis of different cervical lordosis measurement methods in AS, and shows that the Cobb C1-C7 method provides a reliable means for measuring cervical lordosis in AS.